Multitarget therapy of mycophenolate mofetil and cyclosporine A for induction treatment of refractory lupus nephritis. (July 2018) - Jesus, D; Rodrigues, M; da Silva, J A P; Inês, L
Standard induction therapy for lupus nephritis (LN) with mycophenolate mofetil (MMF) or cyclophosphamide (CYC) is often ineffective. Evidence on rescue induction regimens is scarce. We analyzed efficacy and tolerability of multitarget immunosuppression with MMF and cyclosporine A (CsA) as induction treatment for LN (class III/IV/V) refractory to CYC and/or MMF. We included all six refractory LN patients (class IV = 3, class V = 2, class III = 1) from our 400-patient tertiary Lupus Clinic observed between 2012 and 2015. Four patients had previously received pulse CYC. All six received MMF as first or second induction therapy and CsA was added once failure to reach remission was established. Daily dose of MMF was 2–3 g and CsA was dosed up to 2.6–3.7 mg/kg/day. Mean proteinuria was reduced from 2407 mg/24 hours at the start of the MMF+CsA regimen to 544 mg/day after six months. The mean prednisolone dose was reduced from 17.5 to 6 mg/day after six months of MMF+CsA. Four patients achieved a complete renal response, one patient had a partial renal response and one failed to respond. None of the patients presented with adverse events. These data suggest that adding CsA to MMF can induce complete remission of refractory LN and is well tolerated.